Learning From Good Learners: A Case Study - Lesley Adams; Erik Gasparini (Studies in Self-Access Learning Journal)
This paper describes how motivation, goal-setting and autonomous study can lead to the achievement of objectives in language learning and certification. The learning journey reported was documented through interviews and written accounts received from the research participant. The results achieved and the description of the process might be useful for students and also for teachers and learning advisors wishing to encourage autonomy and reflection in their students.